Zinc sulphide-coated titanium dioxide films as photoanode for dye-sensitized solar cells: Effect of immersion time on its performance. (June 2019) - Sadikin, S.N.; Rahman, M.Y.A.; Umar, A.A.
Abstract: This work deals with the use of ZnS-coated TiO2 films as photoanode in a dye-sensitized solar cell (DSSC). The effect of immersion time of ZnS precursor on the photovoltaic parameters of the device has been investigated. The sample contains dominant anatase and minor ZnS phase. The sample prepared with 60 min of immersion time shows the highest optical reflection in the visible region. The DSSC utilizing the photoanode prepared with 60 min of immersion time demonstrated the highest η of 0.80%. This is due to this device has the smallest charge transfer resistance at the interface of Pt/electrolyte that is 0.48 Ω. The energy level diagram and charge transport process in the device with the structure ITO/TiO2 /ZnS/N719/I − -I3 - /Pt/FTO are also presented in the manuscript. Highlights: ZnS-coated TiO2 has been prepared and utilized as photoanode of DSSC. The sample contains dominant anatase and minor ZnS phase. The device demonstrated the highest η of 0.80%. The energy level diagram and charge transfer mechanism are presented.